Persistent Low Level Viraemia in Antiretroviral Treated Patients: Associated Factors and Virologic Outcome among HIV-1 Infected Patients at Nyakach County Hospital - Oketch, James Onyuro; Onguru, Daniel; Ogolla, Sydney; Shiluli, Clement (Global Scientific Journals, 2022)
Antiretroviral treatment (ART) assists patients in controlling their HIV infection and ensuring long-term survival. Despite this advantage, a significant number of HIV-positive individuals do not attain full virologic suppression. The purpose of this research was to determine the prevalence of low-level viraemia, its impact on outcome, and related factors in HIV-1 infected patients receiving ART at Nyakach County Hospital in Kisumu, Kenya. This observational cohort research included HIV-1-infected persons who were registered at Nyakach County Hospital between January 2005 and February 2018 and were receiving WHO-recommended antiretroviral therapy (ART) regimens and viral load monitoring. Persistent low-level viremia is defined in the 2018Kenya ART guidelines as having a detectable VL (above the low detectable threshold) but less than 1,000 copies/mL on two or more consecutive tests. The World Health Organization's (WHO) recommendations for low and middle-income countries (LMIC) define virologic failure as plasma HIV-RNA concentrations more than 1000 copies/mL. The outcomes of this study were viral failure and its related factors. Cox proportional hazard models were used to assess risks. The analysis comprised 738 individuals on first-line antiretroviral therapy, of whom 81 encountered virologic failure and 657 did not. The median duration of ART in the virologic failure group was 6.6 years (IQR 3.5–9.5), while in the non-failure group it was 7.2 years (IQR 4.4–9.7). Increased likelihood of virologic failure was related with higher levels of low-level viraemia (hazard ratio [HR] 9.87, 95% confidence interval [CI] 4.32-22.54; p0.001) compared to virological suppression of fewer than 50 copies/mL. A longer duration of antiretroviral therapy was related with a 38% reduction in the probability of virologic failure (hazard ratio [HR] 0.62, 95% confidence interval [CI] 0.55-0.68; p0.001). Low-level viraemia occurred at a rate of 35.4 per 100 person years of follow-up. Low-level viremia of 500–999 copies/mL at baseline is linked with an increased probability of virologic failure during follow-up in this group.
Keywords: Viraemia; Antiretroviral Therapy; HIV; Kenya